Self-watering plant / Nurisha Hania Kamarudin and Siti Nur Syafirah Roshdi - Kamarudin, Nurisha Hania; Roshdi, Siti Nur Syafirah (2015)
Self-watering plant is an alternative method to watering plant. Soil moisture sensor is used to sense the condition of soil. When soil in dry condition, water will flow out to the plant till the plant received enough water then water will stop flowing through the tube that placed around the flower pot. We are using 3 type of water source which are from rain barrel, sink such water from washing dishes, vegetables, and rice and finally direct water. Water from rain barrel and sink will flow to the tank which placed a stir that function to prevent water from precipitate. Water from direct pipe will use only when there is no water flow from both sources. Finally, water pump is used to pump water out from the tube to the plant. If there is no water source, a water level detector will buzz an alarm to inform users that the tank needs to be refilled water. If there is no alarm buzzed on that is mean water is continuously flow from rain barrel or washing dishes or pipe water. This project will function only if the plant in dry condition which to allow water flow and prevent plant from withered and died. Besides that, the purpose of our project is watering for systematic way and managing water resources which save energy. It also creates to help people manage their time, money and energy.